2004
DOI: 10.1002/ajpa.10277
|View full text |Cite
|
Sign up to set email alerts
|

Enamel thickness of deciduous and permanent molars in modern Homo sapiens

Abstract: This study presents data on the enamel thickness of deciduous (dm2) and permanent (M1-M3) molars for a geographically diverse sample of modern humans. Measurements were recorded from sections through the mesial cusps of unworn teeth. Enamel is significantly thinner on deciduous than on permanent molars, and there is a distinct trend for enamel to increase in relative thickness from M1 to M3. The relatively thicker enamel of M2s and especially M3s can be related to the overall reduction in size of more distal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
8
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(182 citation statements)
references
References 54 publications
9
159
8
6
Order By: Relevance
“…However, Schwartz (2000a) suggested that the majority of published data on enamel thickness in modern humans are derived from European populations, which may not be representative of the species mean and may underestimate variation. A more recent investigation of enamel thickness in disparate modern human regional populations found values similar to those reported for European populations, with low levels of variation within and among populations (Grine, 2002(Grine, , 2005. Differences in enamel thickness between populations or subspecies of non-human primates have not previously been studied.…”
Section: Variation and Patterning Of Enamel Thicknessmentioning
confidence: 78%
See 4 more Smart Citations
“…However, Schwartz (2000a) suggested that the majority of published data on enamel thickness in modern humans are derived from European populations, which may not be representative of the species mean and may underestimate variation. A more recent investigation of enamel thickness in disparate modern human regional populations found values similar to those reported for European populations, with low levels of variation within and among populations (Grine, 2002(Grine, , 2005. Differences in enamel thickness between populations or subspecies of non-human primates have not previously been studied.…”
Section: Variation and Patterning Of Enamel Thicknessmentioning
confidence: 78%
“…Finally, data on relative enamel thickness in enlarged samples of Pan and Pongo were compared to data from a smaller sample of Gorilla. These results were considered in the context of recent studies of crosssectional enamel thickness in modern human molars (Grine, 2002(Grine, , 2005 and enamel volume in hominoid molars (Kono, 2004).…”
Section: Aimsmentioning
confidence: 96%
See 3 more Smart Citations